2011
DOI: 10.1089/jmf.2010.0141
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Antioxidant and Antimicrobial Compounds of Lippia Species by Bioautography

Abstract: The methanolic extracts of the leaves of Lippia species (L. pseudo-thea, L. hermannioides, L. alba, L. rubella, and L. sidoides) were tested for their antibacterial, antifungal, and antioxidant activity. Cytotoxicity was determined by using brine shrimp lethality bioassay. Phytochemical screening was also performed. The extracts showed a minimum inhibitory concentration (MIC) ranging from 78 to 5000 μg/mL for antibacterial activity against at least 2 species of bacteria, although none was active against Escher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 21 publications
2
13
0
1
Order By: Relevance
“…The technique used to determine these antifungal activities was bio-autography and indicated that the antioxidant activity of the extracts was due to coumarins and flavonoids. Terpenoids and the same flavonoids were associated to the observed antimicrobial properties (Fabri, Nogueira, Moreira, Bouzada, & Scio, 2011). Our results confirmed the antimicrobial potential of Lippia spp.…”
Section: Antifungal Assaysupporting
confidence: 84%
“…The technique used to determine these antifungal activities was bio-autography and indicated that the antioxidant activity of the extracts was due to coumarins and flavonoids. Terpenoids and the same flavonoids were associated to the observed antimicrobial properties (Fabri, Nogueira, Moreira, Bouzada, & Scio, 2011). Our results confirmed the antimicrobial potential of Lippia spp.…”
Section: Antifungal Assaysupporting
confidence: 84%
“…Timol and DMSO (the vehicle) were tested at the same concentrations used for EOLC. The tubes were kept at room temperature and mortality was evaluated after 24 h (Fabri et al, 2011). Statistical analysis to adjust death percentage was performed using Wilcoxon and Lichfield method through Probit analysis (Finney, 1971), permitting the determination of LC50 (50% lethal concentration of nauplii).…”
Section: Hatching Of Brine Shrimp Larvaementioning
confidence: 99%
“…Studies have shown the essential oil of L. sidoides have antiparasitic action against ticks (Gomes et al, 2012(Gomes et al, , 2014, forms of Leishmania (Oliveira et al, 2009;Farias-Júnior et al, 2012), helminths from caprine and ovine animals (Camurç a-Vasconcelos et al, 2007) and monogenoideans from Oreochromis niloticus (Hashimoto et al, 2016), and activity against fungi and bacteria (Fabri et al, 2011;Fernandes et al, 2012;Funari et al, 2012;Fontenelle et al, 2007). However, L. sidoides has not been used against monogenoideans from Colossoma macropomum Cuvier, 1818 (tambaqui), an important fish for the fish farming of the region of Amazon.…”
Section: Introductionmentioning
confidence: 99%